Mebendazole and temozolomide in patients with newly diagnosed high-grade gliomas: results of a phase 1 clinical trial - Gallia, Gary L (Neurooncol Adv, 2020)
BACKGROUND: Mebendazole is an anthelmintic drug introduced for human use in 1971 that extends survival in preclinical models of glioblastoma and other brain cancers. METHODS: A single-center dose-escalation and safety study of mebendazole in 24 patients with newly diagnosed high-grade gliomas in combination with temozolomide was conducted. Patients received mebendazole in combination with adjuvant temozolomide after completing concurrent radiation plus temozolomide. Dose-escalation levels were 25, 50, 100, and 200 mg/kg/day of oral mebendazole. A total of 15 patients were enrolled at the highest dose studied of 200 mg/kg/day. Trough plasma levels of mebendazole were measured at 4, 8, and 16 weeks. RESULTS: Twenty-four patients (18 glioblastoma and 6 anaplastic glioma) were enrolled with a median age of 49.8 years. Four patients (at 200 mg/kg) developed elevated grade 3 alanine aminotransferase (ALT) and/or aspartate transaminase (AST) after 1 month, which reversed with lower dosing or discontinuation. Plasma levels of mebendazole were variable but generally increased with dose. Kaplan–Meier analysis showed a 21-month median overall survival with 41.7% of patients alive at 2 years and 25% at 3 and 4 years. Median progression-free survival (PFS) from the date of diagnosis for 17 patients taking more than 1 month of mebendazole was 13.1 months (95% confidence interval [CI]: 8.8–14.6 months) but for 7 patients who received less than 1 month of mebendazole PFS was 9.2 months (95% CI: 5.8–13.0 months). CONCLUSION: Mebendazole at doses up to 200 mg/kg demonstrated long-term safety and acceptable toxicity. Further studies are needed to determine mebendazole’s efficacy in patients with malignant glioma.